Digital literacy, phubbing, and mental well-being in the digital age: a study on young university athletes - Tek, Tolga; Özsari, Arif (Frontiers in Psychiatry, 2025)
Digital literacy has now emerged as a pivotal determinant of individuals’ social, psychological, and mental responses in contemporary society. This study examined the relationships between digital literacy, phubbing behaviors, and mental well-being among young university athletes. The sample consisted of 224 students (mean age = 20.91; SD = 1.98) from the sports sciences faculty of a state university, including 109 females (48.7%) and 115 males (51.3%), who participated voluntarily. Three validated measurement instruments were employed, with confirmatory factor analysis conducted to establish scale reliability and validity. Statistical analyses included descriptive statistics, correlation analysis, and regression analysis to explore variable relationships within the research model. Correlation analysis detected a significant positive moderate relationship between digital literacy and mental well-being (r = .363), alongside a significant negative weak correlation between digital literacy and self-isolation, a phubbing sub-dimension (r =-.133). Regression analyses demonstrated that digital literacy significantly predicts both mental well-being (β =.363) and phubbing-related self-isolation (β = -.133). The findings imply that enhanced digital literacy may mitigate phubbing behaviors while simultaneously promoting mental well-being among young athletes. The implications for digital citizenship education and athlete development programs should be discussed.